2020
DOI: 10.3389/fphar.2020.00301
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 Receptor Antagonist Clopidogrel Attenuates Lung Inflammation Triggered by Silica Particles

Abstract: Silicosis is an occupational lung disease caused by inhalation of silica particles. It is characterized by intense lung inflammation, with progressive and irreversible fibrosis, leading to impaired lung function. Purinergic signaling modulates silica-induced lung inflammation and fibrosis through P2X7 receptor. In the present study, we investigate the role of P2Y 12 , the G-protein-coupled subfamily prototype of P2 receptor class in silicosis. To that end, BALB/c mice received an intratracheal injection of PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It has been shown that macrophages, and inflammatory mediators, including IL-1β and TNF-α, could contribute to exacerbating lung fibrosis [ 39 ]. Besides, previous studies have suggested that AMPK could attenuate lipopolysaccharide (LPS)-stimulated pro-inflammatory factors and increase anti-inflammatory cytokine levels by reducing the transcription activity of nuclear factor-kappaB (NF-κB) in macrophages [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that macrophages, and inflammatory mediators, including IL-1β and TNF-α, could contribute to exacerbating lung fibrosis [ 39 ]. Besides, previous studies have suggested that AMPK could attenuate lipopolysaccharide (LPS)-stimulated pro-inflammatory factors and increase anti-inflammatory cytokine levels by reducing the transcription activity of nuclear factor-kappaB (NF-κB) in macrophages [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies employing administration of higher doses of silica (20 mg/kg) demonstrated that histological alterations in the lung were accompanied by robust increases in pro-inflammatory cytokines [42,43]. Thus, we sought to determine whether the lower dose of silica employed here elicited a similar response.…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that macrophages, and in ammatory mediators, including IL-1β and TNF-α, could contribute to exacerbating lung brosis [34]. Thus, we detected the levels of in ammatory mediators in silica-stimulated macrophages by qRT-PCR analysis.…”
Section: Metformin Attenuates Sio2-induced Cell Cytotoxicitymentioning
confidence: 91%